Employee Performance Improvement through Affective, Normative, and Continuance Commitment With Intrinsic Motivation Mediation - Karyono, Slamet; Hakim, Abdul (Journal of Public Administration and Governance, 2022)
Performance of ROE (Regional Owned Enterprises) employees in Demak Regency can be seen from the decline in the performance of ROE itself, where the decline in performance is seen by changes in income and profit targets which tend to decrease from the initial target of 4 Regional Owned Enterprises, not all ROEs can distribute dividends to owners and the investment ratio in generating dividends is not maximized. The study was conducted by purposive sampling on 103 people who work in various ROE in Demak. The research method used is the Outer and Inner Model on Structural Equational Modeling Partial Least Square (SEM-PLS). The results showed that there was a positive influence of affective, normative, and continuance commitment on intrinsic motivation. Affective, normative, and continuance commitments also have a positive effect on performance. There is a positive influence of intrinsic motivation on performance. Intrinsic motivation positively mediates the relationship of the affective, normative, and ongoing commitment to performance. ROE parties are expected to continue to build commitment to both affective, normative, and sustainable employees and good management so that they can continue to improve performance which ultimately improves the performance of ROE.